PENGARUH KOMUNIKASI, MOTIVASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PT SANDANG ASIA MAJU ABADI SEMARANG - Anin Dwi Jayanti, 09.05.51.0025 (Students Journal of Economic and Management, 2013)
This study aimed to examine the effect of communication, motivation and career development on employee performance at PT Sandang Asia Maju Abadi Semarang. The population as many as 658 employees with a sample of 100 respondents. In this study, the sampling technique used is random sampling. The questionnaire was tested using Validity and Reliability. The results prove that all items declared valid and reliable statement. Subsequent analyzes were tested using multiple linear regression and the results prove that the communication have an effect on by significant to employee performance, motivation have an effect on by significant to employee performance. and career development have an effect on by significant to employee performance.Keywords: communication, motivation, career development, employee performance.